Pengaruh Model PBL Berbantuan Media Animaker terhadap Keterampilan Berpikir Kritis Ekonomi - Puput Apriyani; Kristiani Kristiani; Leny Noviani (Departement of Mathematics Education, 2022)
This study intends to determine the influence and difference in the average economic critical thinking ability of students in general at SMAN 1 Sukoharjo from the use of the PBL model equipped with animaker media. This research is quantitative and quasi-experimental in the form. The research sample was class XI students of SMAN 1 Sukoharjo consisting of 36 students and 35 students, class XI IPS 4 and class XI IPS 3. The cluster random sampling technique is used to select research samples, while tests, observations, and documentation are used to collect research data. This study used t-test of paired samples and ANOVA as a data analysis method. The research findings are as follows: (1) The application of the PBL approach with the use of animaker media affects students' economic critical thinking skills. (2) In classes that use the PBL paradigm assisted by animaker media, there are differences in students' economic critical thinking skills.